An Untold Experience of Exile: New Archival Findings on Felice Brancacci - Pellegrino, Deborah (Renaissance and Reformation / Renaissance et Réforme, 2024)
The story of well-known patrician and merchant Felice Brancacci after his exile from Florence in 1435 has hitherto gone untold. This article offers the first scholarly analysis of newly uncovered letters, account books, and a will composed by Felice after his banishment. These documents convey Felice’s lived experience of exile, highlighting how he navigated his social, political, and commercial roles in central Italy by networking with merchants and elites as well as his sense of isolation and devastating loss. The study contributes to our understanding of the experiences of a remarkable number of political exiles from Florence, and from Italian city states more broadly, during the Renaissance.